Marriage among category of freed women in the city society of Algiers during the ottoman era between 1800-1830 - alouache, fatiha (The Algerian Historical Journal, 2026)
Some marginalized groups in society ,such as slaves and freedmen ,did not receive adequate studies during the Ottoman period, and perhaps this is what motivates us to search for the fate of the freed slaves especially the category of freed women which occupied an important place in the society of the city of Algiers during the first half of the 19th century ,as a result of the growing phenomenon of Manumission ,which liberated the freed woman from the bondage of slavery and made her a free woman ,but at the same time left her bound by her past through her title and the continuation of her relationship with her master .Therefore , it was important to identify the reality of this category of women , and to extract the difficulties they faced in order to rise in society and integrate into it through marriage